Multi-Track Diplomacy Fiqh of Nahdlatul Ulama in Countering Islamophobia in Netherlands - Taufiq, Muhammad; Harisudin, Muhammad Noor; Maimun, Maimun (AHKAM : Jurnal Ilmu Syariah, 2022)
Islamophobia is a global issue, leading to discrimination, violence, and hatred against Muslims in the Netherlands. In response to this, the Special Branch of Nahdlatul Ulama of the Netherlands (PCINU of the Netherlands) is among the Indonesian diaspora campaigning for the moderation of “Islam Nusantara” through multi-track diplomacy fiqh, a holistic approach emphasizing interdependence in politics, economics, and socio-culture. This paper discusses the  multi-track  diplomacy  fiqh  of  PCINU  of  the  Netherlands  in  fighting against Islamophobia in the country. As a non-governmental socio-religious organization, PCINU of Netherlands play a role and strategy in assisting the diplomacy of the Ministry of Foreign Affairs of the Republic of Indonesia in spreading  the  “Islam Nusantara”  idea  to  counter  Islamophobia.  This  article is  based  on  empirical  research  with  fiqh  al-siyāsah and maqāṣid  al-sharī’ah analysis.  This  study  finds  that,  in  countering  Islamophobia,  PCINU  of  the Netherlands  uses  a  multi-track  diplomacy  strategy  that  successfully  spreads friendly, anti-terror, tolerant and moderate Islam. Even though PCINU has not  fully  employed  all  Multi-track  fields,  it  has  successfully  encountered islamophobia and promoted peaceful Islam through Islam Nusantara.Keywords: multi-track Diplomacy Fiqh; Moderation; Islamophobia; Islam Nusantara; world peace AbstrakIslamofobia  menjadi  isu  global  yang  menimbulkan  diskriminasi, kekerasan,  dan  kebencian  terhadap  Muslim,  termasuk  di  Belanda.  Dalam merespons  hal  ini,  Pengurus  Cabang  Istimewa  Nahdlatul  Ulama  Belanda (PCINU  Belanda)  sebagai  diaspora  Indonesia  mengampanyekan  moderasi Islam  Nusantara  melalui  fikih  diplomasi  multitrack. Tulisan ini mendalami strategi  fikih  diplomasi  PCINU  Belanda  dalam  memerangi  Islamofobia  di Belanda. Sebagai organisasi sosial keagamaan non pemerintah, PCINU Belanda memiliki peran dan strategi dalam membantu diplomasi Kementerian Luar Negeri  Republik  Indonesia  dalam  menebarkan  moderasi  “Islam  Nusantara” merespons Islamofobia. Studi ini adalah penelitian empiris dengan pendekatan fikih siyasah dan maqāṣid al-sharī’ah. Dalam merespons Islamofobia, PCINU Belanda menggunakan strategi diplomasi multitrack yang berhasil menebarkan Islam  yang  ramah,  anti  teror,  toleran,  dan  moderat.  Meskipun  PCINU belum sepenuhnya menggunakan semua bidang multitrack, namun berhasil menghadapi  islamofobia  dan  mempromosikan  Islam  yang  damai  melalui Islam Nusantara.Kata Kunci: multi-track diplomacy; moderasi; islamfobia; Islam Nusantara; perdamaian dunia